Problems of phraseology in English linguistics - Amirkulova .N.A (International Consortium of Education and Culture Research Studies, 2019)
This paper makes analyses of the research on the problems of phraseology in English linguistics. On this case, research based on the different points of the English linguistics points of the phraseology. Finally, it concludes with both findings and shortcomings of the issue at all.